Chemoselective and Highly Sensitive Quantification of Gut Microbiome and Human Metabolites. Issue 43 (17th September 2021) - Lin, Weifeng; Conway, Louis P.; Vujasinovic, Miroslav; Löhr, J.‐Matthias; Globisch, Daniel
Abstract: The microbiome has a fundamental impact on the human host's physiology through the production of highly reactive compounds that can lead to disease development. One class of such compounds are carbonyl‐containing metabolites, which are involved in diverse biochemical processes. Mass spectrometry is the method of choice for analysis of metabolites but carbonyls are analytically challenging. Herein, we have developed a new chemical biology tool using chemoselective modification to overcome analytical limitations. Two isotopic probes allow for the simultaneous and semi‐quantitative analysis at the femtomole level as well as qualitative analysis at attomole quantities that allows for detection of more than 200 metabolites in human fecal, urine and plasma samples. This comprehensive mass spectrometric analysis enhances the scope of metabolomics‐driven biomarker discovery. We anticipate that our chemical biology tool will be of general use in metabolomics analysis to obtain a better understanding of microbial interactions with the human host and disease development. Abstract : Chemoselective probes based on stable isotope labeling allow for highly sensitive mass spectrometric quantification and detection of metabolites at attomole quantities in three human sample types.